Buddhism, Democracy and Dr. Ambedkar: The Building of Indian National Identity - Solanki, Milind Kantilal; Ratad, Pratap B. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Today, people feel that democratic values are in danger and so is the nation under threat. Across nations we find different systems of government which fundamentally take care of what lies in their geographical boundaries and the human lives living within it. The question is not about what the common-man feels and how they survive, but it is about their liberty and representation. There are various forms of government such as Monarchy, Republic, Unitary State, Tribalism, Feudalism, Communism, Totalitarianism, Theocracy, Presidential, Socialism, Plutocracy, Oligarchy, Dictatorship, Meritocracy, Federal Republic, Republican Democracy, Despotism, Aristocracy and Democracy. The history of India is about ten thousand years and India is one of the oldest civilizations. The democratic system establishes the fundamental rights of human beings. Democracy also takes care of their representation and their voice. The rise of Buddhism in India paved the way for human liberty and their suppression from monarchs and monarchy. The teachings of Buddha directly and indirectly strengthen the democratic values in Indian subcontinent. The rise of Dr. Ambedkar on the socio-political stage of this nation ignited the suppressed minds and gave a new hope to them for equality and equity. India got independence in the year 1947 and became one of the democratic nations. The new value system gave equal opportunities to all Indians despite of their gender, caste or religion. The present paper discusses the rise of Buddhism and the democratic values present in Buddhism. It also discusses the efforts of Dr. Ambedkar in establishing democratic system in India. It also encompasses the result generated through religion of the Buddha and Dr. Ambedkar to restore the democratic structure again in India.